Menilai Kualitas Laba Perusahaan Melalui Instrumen Analisa Du Pont - Synthia Madyakusumawati; Andy Yulius (Jurnal Akuntansi Bisnis, 2017)
Earnings quality refers to the relevance of earnings in measuring company performances. This research tried to explain phenomena’s of the financial reporting quality, especially responsiveness of Earnings Quality, that is determined by factors efficiency of operating, investing, financing activities.One of the technical approach for earning quality evaluation is a DuPont System. DuPont formula stated the quality of company performance evaluate by Return on Equity Ratio. Excelsior of Return on Equity reflect the higher of company performances in earnings production.Key Words : Earnings Quality, DuPont system, ratio analytics